Cognitive health care system and its application in pill‐rolling assessment. (6th June 2019) - Shah, Syed Aziz; Yang, Xiaodong; Abbasi, Qammer H.
Abstract: Directional antennas have been extensively used in wireless sensor networks (WSNs) for various applications. This work presents the application of a four‐beam patch antenna as a sensor node to assess the pill‐rolling effect in Parkinson disease. The four‐beam patch is small in size, highly directive, and can suppress the multipath fading encountered in indoor settings that adversely affects the measurements. The pill‐rolling effect refers to tremors in the hands, particularly in the forefinger and the thumb, which the patient involuntary rubs together. The core idea is to develop a low‐cost framework that effectively evaluates the particular movement disorder to assist doctors or clinicians in carrying out an objective assessment using the S‐band sensing technique leveraging small wireless devices operating at 2.4 GHz. The proposed framework uses the perturbations in amplitude and phase information to efficiently identify tremors and nontremors experienced in the fingers. The unique imprint induced by each body motion is used to determine the particular body motion disorder. The performance of the framework is evaluated using the support vector machine algorithm. The results indicate that the framework provides high classification accuracy (higher than 90%).